The Effect of Market Return, Rupiah Exchange Rate, and COVID-19 Cases on Stock Returns of Pharmaceutical Companies Listed on IDX - Nike Antika Putri; Aimatul Yumna (Financial Management Studies, 2021)
This study aims to determine the effect of Market Return, Rupiah Exchange Rate, and COVID-19 Cases on stock returns of Pharmaceutical sub-sector companies listed on the IDX. The population of this study amounted to 11 companies. The number of samples in this study was 9 companies which were determined based on the purposive sampling technique. This study uses quantitative research methods using secondary data. The data analysis technique used multiple linear regression. The results showed that simultaneously the return of the JCI, Rupiah Exchange, Daily Positive COVID-19 Cases, and Daily COVID-19 Death Cases had a significant effect on stock returns. While partially JCI returns have a significant effect to all pharmaceutical companies, the rupiah exchange rate only has a significant effect on stock returns for some issuers (DVLA, INAF, KLBF), positive COVID-19 cases only affect INAF returns, and daily COVID-19 death cases do not affect stock returns pharmacy.